Pesquisa e desenvolvimento de nanocompósito constituído por embalagens recicladas e óxido de grafeno para aplicação em impressão 3D - Tegon, Carolina Comin (2017)
The main objective of this work was to research and develop a polymer nanocomposite consisting of its matrix, recycled multilayer flexible packaging and of its dispersed phase, graphene oxide, for application in 3D printing. Flexible multilayer packaging underwent to a recycling recycling process and the incorporation of graphene oxide. For this, the processes of melting of the polymer and the incorporation of the graphene oxide were applied. Further, analyses were performed to characterization of the polymer matrix and the graphene oxide separately and both mixed through for tests such as X-ray diffraction (XRD), infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), energy dispersive x-ray spectroscopy (EDS) and thermogravimetric analysis (TGA), for the morphological characterization such as scanning electron microscopy (SEM) and optical microscopy (OM), for rheological characterization, melt flow index (MFI), and for characterization of mechanical properties such as tensile strength and impact. The obtained results showed that with the incorporation of the graphene oxide in the polymer matrix, properties such as the reduction of density and improvements in the melt flow index and the impact resistance, make the nanocomposite developed interesting for the 3D printing process.